The Influence of Muslim Influencers on Public Purchasing Interest in Halal Products in E-Commerce - Rania Ningsih; Vifin Nadzary A; Nadhiriotul Jannah; Kholilur Rohman; Anvio Dzul Cahyono Issudi; Hawa Gazani (Al-Abqori: Journal of Islamic Thought Studies, 2025)
The development of digital technology and the increasing use of e-commerce have changed people's consumption patterns, especially in choosing halal products. Muslim consumers are increasingly selective about product halalness, not only in food and drinks, but also cosmetics, medicines and fashion. In this context, Muslim influencers have an important role in shaping buying interest through content that combines promotion with Islamic values. This research aims to analyze the influence of Muslim influencers on people's buying interest in halal products in e-commerce. The results of the study show that religious credibility, similar values, level of trust, and Islamic educational content shared by influencers have a significant influence on consumer purchasing interest. Factors supporting this influence include increasing halal awareness, the trend of emigrating the younger generation, the digital Muslim community, and support for government regulations. However, there are also inhibiting factors such as inconsistency in the image of influencers, excessive promotional content, price sensitivity, and the risk of fake influencers. In conclusion, marketing strategies through Muslim influencers have proven effective in increasing interest in buying halal products in e-commerce, as long as they are based on integrity and conformity with the principles of Islamic law.